The Sustainability, Environmental Management and Green Innovation : Industrial Business’ in Thailand: Industrial Business’ - Klinkhajon, Sukanda (วารสารสังคมศาสตร์และมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2020)
The aim of this research was to develop the structural equation model on sustainable performance and its determinants. Specifically, it examined the direct effect of environmental management factor, green innovation and competitive advantage on the sustainable performance. It also aimed at studying the indirect effect of environmental management factor and, green innovation on the sustainable performance of industrial business in Thailand. The population used in the research included 240 of entrepreneurs, top executives, innovation managers, and environmental managers in industrial business who were certified by ISO14001 standard in Thailand. Questionnaire was used as a tool for data collection. The data was analyzed by inferential statistics using structural equation model. The results indicated that competitive advantage had a significantly positive effect on sustainable performance. Environmental management, green innovation had the significantly positive direct effect on competition, both environmental management had the significantly positive direct effect toward green innovation. Moreover, competitive advantage is a significant mediator between environmental management and green innovation on sustainable performance. These findings illustrate that industrial business in Thailand could achieve sustainable performance by developing environmental management, green innovation to develop their competitive advantage.